STUDI PERILAKU PENGGUNAAN EARPLUG PADA PEKERJA BAGIAN FORMING DI PT X KABUPATEN DEMAK - Muhammad Zaefani Aedy; Ekawati Ekawati; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2015)
A Study Of Earplug Use By The Workers Of Forming Department In X Company Demak Regency: Along with the advanced civilization, then, industrial activity turns into the use of machine, tools, installation, transportation and dangerous materials. X company uses production machine that causes noise. Overabundance noise causes health problems. Based on preliminary survey that has been done by the researcher before, the noise has happened in the company from the first time the company was established. The company applies silencer, administrative control, and earplugs to minimize noise exposure in its working environment. The purpose of this research was to analyze the factor of earplug use by the workers of forming department in X Company. The method that was used in this research is qualitative research that involves six informants, which consists of four main informants and two triangulation informants. The data collection was done through the direct observation and in-depth interviews using questionnaires. Result showed, there was no conformity between responsibility and the use of actual personal protective equipment. The company was suggested to maintain the commitment and the written regulation pertaining to the use of earplug and disseminate them to all of the workers. In addition, the control must be enhanced not just by briefing.